Update on recommendations for eligibility of government subsidization of biologic disease‐modifying antirheumatic drugs for the treatment of axial spondyloarthritis in Singapore. (24th November 2019) - Phang, Kee Fong; Lahiri, Manjari; Fong, Warren Weng Seng; Leong, Keng Hong; Leung, Ying Ying; Lim, Anita Yee Nah; Lui, Nai Lee; Manghani, Mona; Tan, Teck Choon; Santosa, Amelia; Sriranganathan, Melonie Kannamma; Suresh, Ernest; et al.
Abstract: Aims: The field of axial spondyloarthritis (axSpA) has undergone significant changes recently in particular with disease classification, assessment of disease activity and increased treatment options for biologics. In order to reflect these developments, we aimed to update the local consensus recommendations for subsidization of biologics. Methods: A modified Delphi approach was used. Six published guidelines from major rheumatology societies and healthcare authorities on axSpA were reviewed. Findings were synthesized and used in formulating updated recommendation statements. Recommendations were rated by 10 practicing rheumatologists in Singapore. Consensus was reached if there was more than 70% agreement or disagreement. Results: Ten statements achieved consensus. Patients may be considered for subsidization of biologic therapy if they fulfill the Assessment of Spondyloarthritis International Society or modified New York criteria, with persistently active disease (defined either by Ankylosing Spondylitis Disease Activity Score ≥ 2.1 or Bath Spondylitis Disease Activity Index ≥ 4), despite 4 weeks of full‐dose non‐steroidal anti‐inflammatory drugs and regular exercise. Either tumor necrosis factor inhibitors or interleukin 17 inhibitors may be used as first‐line therapy, and should be continued if adequate response is achieved at 6 months. Conclusion: Recommendation statements were formulated through a formal consensus process by local experts with a view to assist relevant authorities in funding considerations and for use in clinical practice.